Task shifting approach led by general practitioners to improve maternal and reproductive health care: Experience of rural Nepal - Dangal, Binod; Ghimire, Rajan; Yadav, Santosh (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Task shifting approaches have been the key strategies around the world to reduce maternal, neonatal, and reproductive morbidity as well as mortality. In resource-limited settings, access to those care is severely constrained by the unavailability of trained human resources. General practitioners (GPs) are the cornerstone of peripheral hospitals in Nepal to deliver accessible required basic health care including life-saving surgeries. The analysis identifies task shifting activities like anesthesia, antenatal ultrasonography, safe abortion services,collaborative mental health care, and handling of complicated vaginal delivery led by GPs to midwives, doctors, and paramedics at district-level hospitals to improve maternal and reproductive care. Findings indicated improved access to maternal and reproductive health services without compromising outcomes. However, several barriers were found to better support their practice.